PERENCANAAN MAL PELAYANAN PUBLIK DI KABUPATEN SINTANG DENGAN PENDEKATAN ARSITEKTUR TROPIS - Wiliam Andrea; Irwin Irwin; Muhammad Nurhamsyah (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
Public Service Hall is a place where public service delivery activities take place in the form of goods or services and administrative services which are an extension of the function of integrated services both central and regional as well as BUMN/BUMD/private services in order to provide fast, easy, affordable, safe services and comfortable. The district capital is located in Sintang District. This regency has an area of 21,638.00 km² and a population of 421,306 people in 2021. The MPP development is expected to support government activities from an economic function, especially facilitating and accelerating every permit, especially business permits to drive the national economy. MPP development is one of the government's strategies in an effort to improve the quality of public services in a sustainable manner. MPP management is carried out in an integrated and integrated manner to provide fast, easy, affordable, safe, and convenient services for the community. The method used in this planning begins with data collection which is then analyzed to obtain a space program and design concept with the final result in the form of design visualization and design working drawings. The design is located in Sintang District, Sintang Regency, West Kalimantan. The shape of the building is adapted to the climatic conditions in the tropics which have high rainfall. In the external area there is a zone designated for circulation areas, parking for vehicles spread out in open spaces and green open spaces.